Synthesis and crystal structure of (E)-1-benzyl-3-(4-methoxystyryl)quinoxalin-2(1H)-one, C24H20N2O2 - Missioui Mohcine; Essassi El Mokhtar; Mague Joel T.; Ramli Youssef (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C24H20N2O2, monoclinic, P21/c (no. 14), a = 11.1713(3) Å, b = 17.7718(5) Å, c = 10.9852(3) Å, β = 118.990(1)°, V = 1907.67(9) Å3, Z = 4, Rgt(F) = 0.0538, wRref(F2) = 0.1582, T = 296(2) K.